Onset, propagation, and evolution of strain localization in undrained plane strain experiments on clay - Wu, Xingdong (Kansas State University, 2016)
The conventional triaxial test is the primary laboratory test for determining the shear strength of soils. Geotechnical field conditions such as long earth dams, long embankments, long retaining walls, strip foundations, tunnels, and buried pipelines often experience plane strain states of stress. However, stress strain and load deformation responses in plane strain loading differ considerably from responses observed in the conventional triaxial test. Research has shown that soils loaded in a plane strain state are far more sensitive to imperfections than soils tested in a conventional triaxial device. Plane strain loading leads to material instability manifested as sudden localized failure, resulting in decreased load-carrying capacity of the soil and compromised geotechnical and civil infrastructures. Although previous studies have mostly focused on granular materials, this research investigated the plane strain response of clay. An undrained plane strain compression test program was devised to investigate the effects of past stress history and strain rates on strain localization in kaolin clay. Experiments were carried out in a plane strain (or biaxial) device at Northwestern University, Evanston, Illinois. Because the device was heavily internally instrumented, strain localization progress was closely monitored throughout each biaxial test. Clay response in the biaxial test demonstrated three phases: (1) a homogenous response, (2) the onset and propagation of strain localization, and (3) the evolution of strain localization as a shear band. The duration of each phase was determined for each test, and a Lagrange strain tensor was used to obtain the evolution of volumetric and shear strains at the level of a shear band for three tests. Results revealed the development of large strains in these mesoscale structures. Furthermore, evolution of Mohr-Coulomb effective shear strength parameters was traced throughout the propagation and evolution phases by using two different methods. It showed that in clay samples, unlike in granular materials, the post-peak plateau, which is reached by deviatoric stress, corresponds to friction values that are significantly lower than the critical state values. Other researchers who used scanning electron microscope and anisotropy of magnetic susceptibility detected a significant reorientation of clay particles inside shear bands. Their findings combined with findings in this study lead to the conclusion that the sub-meso scale mechanism responsible for large shear strains and a severe reduction in effective friction is a significant reorientation of clay particles inside shear band.
Keywords: Plane strain test; Strain localization; Clay